Pulpotomy of mature teeth: A systematic analysis of the failed cases - Nawaf Almutairi (Elsevier, 2024)
Pulp therapy aims to maintain the health and integrity of teeth and their supporting tissue and preserve the vitality of the tooth pulp affected by dentinal caries or severe traumatic injury. Thus, the best clinical practice provides pulpal health or pathosis diagnosis and various therapeutic interventions evidenced in both the deciduous and permanent dentition for endodontic treatment. The pulp health status determines the type of pulpal therapy used. Vital pulp therapies for primary teeth include protective liners, pulp capping, and pulpotomy for reversible pulpitis; for permanent teeth, pulpotomy can be considered for irreversible pulpitis.For reversible or irreversible pulpitis, invasive management of decayed teeth has traditionally been performed. However, at present, coronal pulpotomy-like vital pulp therapy has led to successful treatment outcomes that are less invasive. Compared to root canal treatments, coronal pulpotomy is cost-effective, less time-consuming, and less technically demanding.The success of a pulpotomy depends on the clinician's experience, appropriate clinical techniques, and materials used. This narrative review provides insights into the systematic analysis of pulpotomy failure, causes and signs of failure, and alternative endodontic interventions.